2020
DOI: 10.1080/16549716.2019.1711336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rural response system intervention to prevent violence against women: findings from a community-randomised controlled trial in the Central Region of Ghana

Abstract: Background: Intimate partner violence (IPV) affects one in three women globally and undermines women's human rights, social and economic development, and health, hence the need for integrated interventions involving communities in its prevention. Objective: This community-randomised controlled trial evaluated the Rural Response System (RRS) intervention, which uses Community Based Action Teams to prevent IPV by raising awareness and supporting survivors, compared to no intervention. Methods: Two districts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 17 publications
0
44
1
Order By: Relevance
“…Further capacity building on gender transformative dialogues and community mobilisation can enhance this work. Studies in Ghana and the United States have demonstrated the effectiveness of interventions to reduce intimate partner violence by raising awareness about violence, counselling couples experiencing violence, conducting safety planning, and providing referrals (Ogum Alangea et al, 2020;Sarin & Lunsford, 2017). However, these interventions involved considerable investments in training and support and raise concerns about overburdening FCHVs with too many responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further capacity building on gender transformative dialogues and community mobilisation can enhance this work. Studies in Ghana and the United States have demonstrated the effectiveness of interventions to reduce intimate partner violence by raising awareness about violence, counselling couples experiencing violence, conducting safety planning, and providing referrals (Ogum Alangea et al, 2020;Sarin & Lunsford, 2017). However, these interventions involved considerable investments in training and support and raise concerns about overburdening FCHVs with too many responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, two randomised controlled trials have demonstrated that CHWs can play an effective role in preventing intimate partner violence through community sensitisation and facilitating access to services. In Ghana, physical violence reported by women decreased in communities where community-based action teams led dialogues at local events on women's economic rights, equitable household practices, and non-violence and also counselled couples (Ogum Alangea et al, 2020). In the United States, study areas showed significant, sustained decreases in intimate partner violence in response to home visits to pregnant women during which a CHW or nurse reviewed information on the cycle of violence, danger assessments, safety planning, and available resources (Sharps et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…3 A growing body of literature has evaluated interventions designed to prevent and reduce IPV and shift gender norms by targeting women, [6][7][8][9] men, 7 10 11 couples [12][13][14] or communities. [15][16][17][18] In general, these interventions entail intensive interactions over a defined period with a particular set of participants. These individuals may be those beneficiaries who are explicitly sampled for and invited to participate in the programme, or, in the case of community-level interventions, those beneficiaries who are effectively reached by the mobilisation process.…”
Section: Key Questionsmentioning
confidence: 99%
“…6 19 The published community-level IPV intervention trials reported community-level effects without separately analysing effects for beneficiaries directly reached by the programme (eg, programme activists or participants), vis-à-vis community members who are exposed indirectly to programme messages. [15][16][17][18] By contrast, a much larger literature has demonstrated spillover effects of other public health interventions including vaccines, infectious disease interventions, and water and sanitation interventions. 20 21 Unite for a Better Life (UBL) is a gender-transformative intervention designed to reduce physical and sexual IPV and HIV risk behaviours and promote healthier, more equitable relationships.…”
Section: Key Questionsmentioning
confidence: 99%
See 1 more Smart Citation